Why Do Firms Pay Antidumping Duty? - Gupta, Poonam (IMF Working Papers; Working Paper, 1999)
With the virtual elimination of tariffs and quotas under GATT, antidumping measures emerged as a key instrument of protection. Under antidumping actions exporters can either raise the price to eliminate the dumping margin or pay an antidumping duty. This paper analyzes the incentives to exporters to choose between duty or settlement outcomes and finds that due to the smaller loss in market share exporters may prefer an antidumping duty over voluntary settlement. The paper analyzes the welfare implications of these outcomes and finds that they are ambiguous.